Material thinking; the theory and practice of creative research - Carter, Paul (Carlton : Melbourne university press, 2004)
- A pattern made of holes : creative research and local invention ##- Bearing witness to the eyewitness ##- As we see them right here ##- Wrong footings ##- An ephemeral architecture ##- Remembering forwards ##- Speaking pantomimes ##- Offcuts of infinity : artistic collaboration and material thinking.
Onderzoek KASK (1KA-OFVR)
boek